Comparison between Early and Standard Oral Feeding After Emergency Bowel Surgery - Shahbaz Khan, Irfan Ahmad, Tariq Jamil, Syed Aamer Hussain, Sarmad Younis, Zakriya Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Laparotomy for small intestinal diseases accounts for a sizable proportion of all emergency operations. The perioperative outcome of these procedures may be enhanced by applying an adapted enhanced recovery after surgery (ERAS) regimen supported by evidence. Aim: This research aimed to appraise the outcomes of near-the-beginning feeding to those of normal eating in patients who had undergone emergency surgery on their digestive tracts (GI) or bowels. Methodology: This study was conducted at the departments of general surgery HMC Peshawar and Nishtar Hospital, Multan. Between November 2021 and April 2022, the data was collected from 84 patients who required emergency intestinal resection and anastomosis. Patients were not eligible if they had short bowel syndrome, intestinal ischemia, protracted bowel perforation, or septic shock. The patients were divided into two groups, those who began eating earlier (group E; n=44) and those who began eating later (group L; n=40). Early feeding entailed starting enteral nutrition within 48 hours of surgery. The surgical and clinical outcomes of the early feeding group were appraised to those of the late feeding cluster. Results: Bowel perforation was the most prevalent reason for surgery, and the miniature intestine was nearly all common areas affected. There was no meaningful difference in the origins, places, or interventions between the two sets of participants. Group L, on the other hand, had a much higher incidence of pulmonary issues (13.6 per cent vs 47.5 per cent, p=0.001) and an extended mean length of stay (LOS) in the ICU (2 days vs 1 day, p=0.038) and hospital (9 days vs 12 days, p=0.012).